Vernacular Landscape in Muslim Community of Thailand and Malaysia - Limthongsakul, Sani (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Vernacular landscape is a unique mixture of cultural and natural environments. One could gain an understanding of the place identity when landscape features of the area are perceptible and in unity. This paper illustrates a way to apprehend and interpret vernacular spatial practice of the local landscape of Muslim community in the four southern border provinces of Thailand and the state of Perak and Penang on the northern Malay peninsula. In observing the vernacular spatial patterns, this paper utilizes an anthropology of space as a method of observation where settlement patterns, village land-use, housing compounds, landscape features and social space will be investigated. By sharing the same geographical area and socio-cultural background where Islamic religion is predominant, thus the local landscape of Thai-Muslim community and local Malays community at the village level possesses similar characteristics. The field surveys revealed that the landscape was altered, adapted and enhanced in response to the local needs in an environmentally and culturally sensitive way. The local land-use and landscape features reflect local wisdom and value of agrarian society and Muslim community. It was found that the agricultural landscape produces socio-cultural space for the community and reflects the local identity of the place.